DESIGNING A HIGH SCHOOL IN MEDAN CITY WITH THE APPLICATION OF BIOPHILIC ARCHITECTURE - Suwantoro, Hajar; Hasibuan , Shifa Chantika Sholawie (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The design of this high school is a strategy to improve the educational infrastructure in order to produce excellent students. The research method used is descriptive data collection. This method involves collecting, reviewing, and analyzing literature studies relevant to the design topic. A literature study was conducted by conducting a comparative study of several buildings to gain an in-depth understanding of the High School. This high school uses the Biophilic architectural theme to create a better environment that is conducive to the health and well-being of its users and supports the excellent curriculum applied to the school to be designed. Biopilik can be reflected in the physical form of the building and its natural environment. The results show that the application of the concept can be taken from several examples with visible design success, achieving a good concept with a relevant theme as well as possible in order to achieve a building that realizes activities optimally for its users.